PENGARUH DIFERENSIASI PRODUK DAN STRATEGI PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Tahu Riossta Kabupaten Pangkalan Kerinci) - Sri Maharani; Abygael Paulina Sijabat (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2024)
This study aims to analyze the effect of Product Differentiation and Promotional Strategy on Purchasing Decisions of Riossta Tofu in Pangkalan Kerinci Regency. The method used is the Non Probability Sampling method with incidental sampling type. Researchers distributed questionnaires to 30 respondents who had become Riossta Tofu customers via Google Form. Data analysis in this study used SPSS V-25. The results of the analysis concluded that product differentiation had a positive effect on purchasing decisions where the calculated t value was greater than the t table of 4.081> 1.703 with a significance level of 0.00 <0.05, and the promotional strategy had a positive effect on purchasing decisions with a t table value of 6.549> 1.703 with a significance value of 0.000 <0.05. The results of the simultaneous test (F-test) indicate that product differentiation and promotional strategy jointly influence purchasing decisions, with a calculated F-value of 32.659, greater than the F-table value of 3.369. The coefficient of determination test yielded an R-squared value of 0.708, indicating that product differentiation and promotional strategy influence purchasing decisions by 70.8%.